Best Practices of Sustainable Development to Make Six Senses Uluwatu a Green Hotel - Adryansyah Pakpahan; I Gusti Agung Mas Krisna Komala; Ni Made Ernawati; Ni Nyoman Triyuni; Ni Wayan Wahyu Astuti; I Ketut Suja (Bali Membangun Bali: Jurnal Bappeda Litbang, 2022)
Purpose: This research aims to describe the implementation of sustainable development practices at Six Senses Uluwatu, Bali, in pursuing a green hotel. Design/methodology/approach: Methods of data collection used are by conducting depth-in interviews, distrib-uting questionnaires to 95 correspondents with incidental sampling technique, and observation. Data analysis method used is qualitative descriptive analysis through transcribing, coding, describing, and interpreting the data. Findings: Six Senses Uluwatu already implemented the best practices of sustainable de-velopment which including recycling waste paper, minimizing consumption and wastage resources, using a green-car electric vehicle, preventing in using dis-posable goods, using environmentally friendly cleaning chemicals, producing owned bottling plant water, practicing organic farming manner, applying zero-waste packaging, providing local employment, and equal opportunities to women and people of all background. Implications: These practices are aligned with the four key themes of Green Globe Standard including sustainable management, cultural heritage, social/economic, and envi-ronmental. Six Senses Uluwatu is eligible to become a green hotel through the implementation of best practices sustainable development at Six Senses Ulu-watu.